2021
DOI: 10.1016/j.esmoop.2021.100290
|View full text |Cite
|
Sign up to set email alerts
|

Avelumab in patients with previously treated metastatic Merkel cell carcinoma (JAVELIN Merkel 200): updated overall survival data after >5 years of follow-up

Abstract: Background: Merkel cell carcinoma (MCC) is a rare, aggressive skin cancer that has a poor prognosis in patients with advanced disease. Avelumab [anti-programmed death-ligand 1 (PD-L1)] became the first approved treatment for patients with metastatic MCC (mMCC), based on efficacy and safety data observed in the JAVELIN Merkel 200 trial. We report long-term overall survival (OS) data after >5 years of follow-up from the cohort of patients with mMCC whose disease had progressed after one or more prior lines of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 7 publications
(24 reference statements)
1
30
0
3
Order By: Relevance
“…It is noteworthy that a slight tendency of improved PFS and OS was shown in patients carrying PD-L1 in a pre-treatment setting and receiving pembrolizumab [ 18 ]. A similar result was found in patients with chemotherapy-refractory MCCs receiving avelumab (cohort A of JAVELIN Merkel 200 study) [ 20 , 103 ]. In addition, in a real-world study, preliminary data analysis on 6 tumoral and plasma samples suggested that serum soluble PD-1 > 3.8 ng/mL, and the presence of PD-L1 and brisk TILs on tumor samples, were associated with a longer time to treatment failure [ 106 ].…”
Section: MCC Immunobiology and Tumor-specific Predictorssupporting
confidence: 76%
See 1 more Smart Citation
“…It is noteworthy that a slight tendency of improved PFS and OS was shown in patients carrying PD-L1 in a pre-treatment setting and receiving pembrolizumab [ 18 ]. A similar result was found in patients with chemotherapy-refractory MCCs receiving avelumab (cohort A of JAVELIN Merkel 200 study) [ 20 , 103 ]. In addition, in a real-world study, preliminary data analysis on 6 tumoral and plasma samples suggested that serum soluble PD-1 > 3.8 ng/mL, and the presence of PD-L1 and brisk TILs on tumor samples, were associated with a longer time to treatment failure [ 106 ].…”
Section: MCC Immunobiology and Tumor-specific Predictorssupporting
confidence: 76%
“…Long-term data from the JAVELIN Merkel 200 trial (part A cohort) showed a median OS of 12.6 months (95% CI 7.5–17.1 months) and a 5-year OS rate of 26% (95% CI 17% to 36%). However, considerable differences in patients with PD-L1+ versus PD-L1- tumors were documented, with a median OS of 12.9 months (95% CI 8.7–29.6 months) and a 5-year OS rate of 28% (95% CI 17% to 40%) in the former versus a median OS of 7.3 months (95% CI 3.4–14.0 months) with a 5-year OS rate of 19% (95% CI 5% to 40%) in the latter [ 103 , 104 ].…”
Section: The Role Of Immunotherapy In Non-melanoma Skin Cancermentioning
confidence: 99%
“…Since PD-L1 is expressed in tumor cells, as well as TAMs and antigen-presenting cells (APCs), to maintain the immunosuppressive microenvironment in cSCC [ 61 ], the anti-PD1 Ab cemiplimab is used for the treatment of locally advanced and metastatic cSCC [ 70 , 71 ]. The objective response rate (ORR) of cemiplimab is 44% [95% confidence interval (CI), 32–55] for locally advanced melanoma [ 4 ], whereas it is 45.2% (95% CI, 35.9% to 54.8%) for metastatic cSCC [ 70 ].…”
Section: Profiles Of Tumor-infiltrating Leukocytes Determine the Char...mentioning
confidence: 99%
“…The objective response rate (ORR) of cemiplimab is 44% [95% confidence interval (CI), 32–55] for locally advanced melanoma [ 4 ], whereas it is 45.2% (95% CI, 35.9% to 54.8%) for metastatic cSCC [ 70 ]. In Merkel cell carcinoma, the anti-PD-L1 Ab avelumab significantly prolonged overall survival (OS) in a PD-L1-highly-expressing cohort [12.9 months (95% CI, 8.7–29)] compared to a low-expressing cohort [7.3 months (3.4–14.0)] [ 71 ]. Moreover, tumor site PD-L1 expression in combination with PD-1-positive cells in TILS is a prognostic factor in CAS [ 66 ].…”
Section: Profiles Of Tumor-infiltrating Leukocytes Determine the Char...mentioning
confidence: 99%
“…Moreover, in the face of a powerful immune reaction, many patients progress or do not respond to modern immunotherapy due to resistance or immunoescape mechanisms. To date, Cemiplimab for cSCCs ( 3 ) and Avelumab ( 15 ) for MCCs have been approved by European Medicines Agency (EMA); recently Food and Drug Administration (FDA) approved Cemiplimab for locally advanced Basal cell carcinoma (LaBCC) ( 16 ) and other drugs are studied through several clinical trials.…”
mentioning
confidence: 99%